2015
DOI: 10.1007/s12020-015-0708-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of early 18F-FDG PET/CT in therapeutic management and ongoing risk stratification of high/intermediate-risk thyroid carcinoma

Abstract: Little is known about the role in ongoing risk stratification of fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) performed early after radioactive iodine (RAI) ablation in differentiated thyroid carcinoma (DTC). The aim of the study is to investigate whether 18F-FDG PET/CT performed early after RAI ablation is useful to detect disease and to influence therapy and ongoing risk stratification. Patients with high/intermediate risk of recurrent DTC were included. 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, FDG-PET/CT is able to exclude recurrence or metastases [ 24 ] and negative FDG-PET/CT could be predictive of a very good response to therapy. [ 25 ] Similar to our findings, other retrospective studies demonstrated that a negative FDG-PET would predict an excellent outcome despite an elevated Tg value. [ 13 , 14 ] Likewise a study on the outcome of medical and surgical management in DTC patients showed that a positive FDG-PET predicts a worse prognosis and can help to distinguish between patients with distant metastases and not candidates for reoperation and patients with localized neck lesions that should be resected.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, FDG-PET/CT is able to exclude recurrence or metastases [ 24 ] and negative FDG-PET/CT could be predictive of a very good response to therapy. [ 25 ] Similar to our findings, other retrospective studies demonstrated that a negative FDG-PET would predict an excellent outcome despite an elevated Tg value. [ 13 , 14 ] Likewise a study on the outcome of medical and surgical management in DTC patients showed that a positive FDG-PET predicts a worse prognosis and can help to distinguish between patients with distant metastases and not candidates for reoperation and patients with localized neck lesions that should be resected.…”
Section: Discussionsupporting
confidence: 90%
“…Few previous studies have also shown that most of the recurrences are noted in the area of the neck and thorax, although most of them have not detailed the sites of distant metastases [ Table 4 ]. [ 18 27 28 29 30 31 32 33 ] In our study, only four patients showed distant metastases to the brain, skull, acetabulum, and sacrum outside the proposed limited PET CT field of view. However, all these lesions were known by previous WBS or clinical history.…”
Section: Discussionmentioning
confidence: 55%
“…At the same time, glucose metabolism activity is enhanced, and glucose transporter-1 (GLUT-1) expression is significantly increased ( 19 ). On the contrary, a low expression of GLUT-1 in differentiated thyroid carcinoma may lead to a decrease in glucose metabolism activity, thus achieving a relatively good prognosis ( 20 ). A previous study has shown that 18 F-FDG PET-CT has a vital reference value for the early diagnosis and prognosis of thyroid cancer ( 21 ).…”
Section: Discussionmentioning
confidence: 99%